HARMONISASI SOSIAL DAN RESOLUSI KONFLIK DALAM KELUARGA PERKAWINAN BEDA AGAMA: ANALISIS MAQASID AL-SYARI’AH TERHADAP KETAHANAN KELUARGA - Rifky Muhammad Farhan; Yosep shihab mufti; Firmansyah (Kampus Akademik Publiser, 2026)
Interfaith marriage is a complex social phenomenon that frequently triggers internal dynamics challenging family resilience. This study aims to analyze how social harmonization and conflict resolution are realized in interfaith marriage families through the lens of Maqāṣid al-Syarī‘ah (the objectives of Islamic law). Employing a qualitative research method with a descriptive-analytical approach, this study examines how interfaith couples navigate theological differences to maintain domestic stability. The results indicate that effective conflict resolution is achieved through assertive communication, active tolerance, and cultural compromise. Within the perspective of Maqāṣid al-Syarī‘ah, efforts to maintain family resilience inherently reflect the protection of the five essential elements (al-darūriyyāt al-khamsah). Despite challenges in collective ḥifẓ al-dīn (preservation of religion), interfaith couples tend to prioritize ḥifẓ al-nafs (preservation of soul/psychological well-being), ḥifẓ al-nasl (preservation of progeny/child-rearing), and ḥifẓ al-māl (preservation of wealth) to generate benefit (maṣlaḥah) and prevent harm (mafsadah). This study concludes that family resilience in interfaith marriages can be sustained if couples are able to contextualize universal values of welfare over their respective theological egos.